Lard and/or canola oil-rich diets induce penile morphological alterations in a rat model - Jorge Luiz Medeiros Júnior; Fabiana Araújo de Oliveira; Pamella Campos Silva; Angélica Furriel; Francisco José Barcellos Sampaio; Bianca Martins Gregório (Acta Cirúrgica Brasileira, 2014)
PURPOSE: To investigate the effect of dietary lipid quantity and/or quality on penis morphology in adult rats. METHODS: Thirty-eight male Wistar rats were divided into 4 groups: normal lipid diet (NL), high-fat diet rich in saturated fatty acids (HF-S), high-fat diet rich in polyunsaturated fatty acids (HF-P), and high-fat diet rich in saturated and polyunsaturated fatty acids (HF-SP). Blood samples were collected and the penises were removed for histomorphometrical and immunohistochemical analysis. RESULTS: All high-fat diets promoted an increase in the body mass (p<0.0001). The HF-S and HF-SP groups presented hyperglycemia (p=0.0060), hyperinsulinemia (p=0.0030), and hypercholesterolemia (p=0.0020). Concerning the penis, the high-fat diets led to an increase in the collagen fibers (p<0.0001) and smooth muscle cell density area (p=0.0027), and a decline in the sinusoidal space density area (p<0.0001) and corpus cavernosum cell proliferation (p=0.0003). CONCLUSION: Diets rich in saturated and/or polyunsaturated fatty acids promoted overweight and induced penile changes in rodent models, which may lead to the development of erectile dysfunction.